Carbohydrate drinks delay fatigue during intermittent, high-intensity cycling in active men and women - Davis, J. M.; Jackson, D. A.; Broadwell, M. S.; Queary, J. L.; Lambert, C. L. (International Journal of Sport Nutrition and Exercise Metabolism, 1997)
The effects of ingesting carbohydrate drinks on fatigue during intermittent, high-intensity cycling in men and women were determined. Physically active but untrained women (n = 7) and men (n = 9) completed one practice trial and two experimental sessions separated by 1 week. Sessions consisted of repeated 1-min cycling bouts on a bicycle ergometer at 120-130% VO2max separated by 3 min rest until fatigue. Carbohydrate (CHO) or placebo (P) beverages (4 ml.kg body weight-1) were ingested immediately before exercise (18% CHO) and every 20 min during exercise (6% CHO). Plasma glucose and insulin were higher, RPE for the legs was lower, and time to fatigue was longer in CHO than P. Men's and women's responses were not different for any variable measured. These data suggest a beneficial role of CHO drinks on performance of intermittent, high-intensity exercise in men and women.